Projected Future Changes of Tropical Cyclone Activity over the Western North and South Pacific in a 20-km-Mesh Regional Climate Model - Zhang, Chunxi; Wang, Yuqing (Journal of climate, 2017)
A high-resolution regional atmospheric model is employed to project the late twenty-first-century changes of tropical cyclone (TC) activity over the western North Pacific (WP) and southwest Pacific (SP). The model realistically reproduces the basic features of the TC climatology in the present-day simulation. Future projections under the representative concentration pathway 4.5 (RCP45) and 8.5 (RCP85) scenarios are investigated. The results show no significant change of TC genesis frequency (TCGF) in the WP by RCP45 due to the cancellation of the reduction over the western part and the increase over the eastern part together with a considerable decrease of TCGF by RCP85 due to the excessive TCGF reduction in the western part. The TCGF over the SP consistently decreases from RCP45 to RCP85. Despite the fact that the simulated maximum surface wind speeds are below 52 m s−1, the change with more strong TCs and fewer weak TCs is robust. The future changes in the TC genesis locations and translational speeds modulate the TC lifetime and frequency of occurrence. The TC genesis potential index (GPI) is used to evaluate the projected TCGF changes. The results show that low-level vorticity and midtropospheric vertical velocity largely contribute to the reduction of GPI in the western part of the WP, while vertical wind shear and midtropospheric vertical velocity mainly contribute to the decrease of GPI over the SP. The weakening of the monsoon trough is found to be responsible for the decreases of GPI and TCGF over the western part of the WP.